Forgotten Actors: Glycoside Hydrolases During Elongation Growth of Maize Primary Root - Nazipova, Alsu; Gorshkov, Oleg; Eneyskaya, Elena; Petrova, Natalia; Kulminskaya, Anna; Gorshkova, Tatyana; Kozlova, Liudmila (Frontiers in Plant Science, 2022)
Plant cell enlargement is coupled to dynamic changes in cell wall composition and properties. Such rearrangements are provided, besides the differential synthesis of individual cell wall components, by the enzymes that modify polysaccharides in muro. To reveal the enzymes which may contribute these modifications and relate them to the stages of elongation growth in grasses, we carried out a transcriptomic study of five zones of the primary maize root. At the initiation of elongation, significant changes occur with xyloglucan: once synthesized in the meristem, it can be linked to other polysaccharides through the action of hetero-specific xyloglucan endotransglycosidases, which expression boosts at this stage. Later, the genes for xyloglucan hydrolases are upregulated. Two different sets of enzymes capable of modifying glucuronoarabinoxylans, mainly bifunctional α-arabinofuranosidases/β-xylosidases and β-xylanases, are expressed in the maize root to treat the xylans of the primary and secondary cell walls, respectively. The first set is highly pronounced at the stage of active elongation, while the second – at elongation termination. Several glycoside hydrolases able to degrade mixed-linkage glucan are downregulated specifically at active elongation stressing the importance of this polymer for cell growth. The possibility that in muro many glycoside hydrolases act as transglycosylases is discussed.